Effect of nedocromil sodium on the airway response to inhaled capsaicin in normal subjects. Issue 11 (November 1988) - Hansson, L; Choudry, N B; Fuller, R W; Pride, N B
Abstract : In six normal subjects treatment with 4 mg nedocromil sodium failed to alter the cough and bronchoconstriction induced by inhaled capsaicin. Because nedocromil has previously been shown to inhibit reflex bronchoconstriction provoked by inhaled sulphur dioxide and inhaled bradykinin, the results suggest that inhaled capsaicin acts on different nerve fibres.